The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1523/jneurosci.0879-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Visual Selection and Posterior Parietal Cortex: Effects of Repetitive Transcranial Magnetic Stimulation on Partial Report Analyzed by Bundesen's Theory of Visual Attention

Abstract: Posterior parietal cortex (PPC) may contribute to visual selection by exerting top-down influences on visual processing. To seek direct evidence for this, we used 10 Hz repetitive transcranial magnetic stimulation (rTMS) over right or left PPC in nine healthy volunteers during a partial (selective) report task that allows quantitative assessment of top-down control and other parameters. Participants reported digits in a relevant color ("targets") but not those in an irrelevant color ("nontargets") from a brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
91
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 69 publications
(86 reference statements)
18
91
2
Order By: Relevance
“…This allowed separate parameters concerning top-down control, sensory effectiveness, and attentional weight to be measured within a single visual task (see Materials and Methods, Data analysis, below). We have previously examined the impact of parietal TMS on Bundesen parameters in this task (Hung et al, 2005). Applying TMS to the left or right human FEF permitted a new comparison between the frontal effects studied here and the parietal effects reported previously (Hung et al, 2005) to further specify the distinct roles of different nodes in the network modulating visual processing.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…This allowed separate parameters concerning top-down control, sensory effectiveness, and attentional weight to be measured within a single visual task (see Materials and Methods, Data analysis, below). We have previously examined the impact of parietal TMS on Bundesen parameters in this task (Hung et al, 2005). Applying TMS to the left or right human FEF permitted a new comparison between the frontal effects studied here and the parietal effects reported previously (Hung et al, 2005) to further specify the distinct roles of different nodes in the network modulating visual processing.…”
Section: Introductionmentioning
confidence: 77%
“…For blocks with TMS, magnetic stimulation was delivered synchronously with the onset of the stimulus array to be reported (during the partial-report or the color-report control task) in a five-burst train at 10 Hz for 500 ms, with a fixed intensity of 60% of maximum stimulator output (corresponding to 86 -115% of the intensity of the resting motor threshold for participants in this experiment, when the same TMS stimulator was applied over M1 outside the experiment). Previous studies have shown that, with these stimulation parameters, such bursts of TMS are able to induce transient disruptions of neural processing in FEF (Muggleton et al, 2003;O'Shea et al, 2004; for effects of the same TMS protocol in the current paradigm when applied over PPC instead of FEF, see Hung et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations